Indomethacin-induced morphologic changes in the rat urinary bladder epithelium - (:unkn) unknown (ELSEVIER SCIENCE INC, 2003)
Objectives. To evaluate the morphologic changes in rat urothelium induced by indomethacin. Nonsteroidal anti-inflammatory drug-induced cystitis is a poorly recognized and under-reported condition. In addition to tiaprofenic acid, indomethacin has been reported to be associated with this condition. Methods. Three groups were established: a control group (n = 10), a high-dose group (n = 10), treated with one intraperitoneal injection of indomethacin 20 mg/kg, and a therapeutic dose group (n = 10) in which oral indomethacin was administered 3.25 mg/kg body weight daily for 3 weeks. The animals were then killed and the bladders removed for light and electron microscopic studies. Results. The light microscopic findings showed some focal epithelial degeneration that was more prominent in the high-dose group. When compared with the control group, both indomethacin groups revealed statistically increased numbers of mast cells in the mucosa (P <0.0001) and penetration of lanthanum nitrate through intercellular areas of the epithelium. Furthermore, the difference in mast cell counts between the high and therapeutic dose groups was also statistically significant (P <0.0001). Conclusions. Indomethacin resulted in histopathologic findings typical of interstitial cystitis, such as leaky bladder epithelium and mucosal mastocytosis. The true incidence of nonsteroidal anti-inflammatory drug-induced cystitis in humans must be clarified by prospective clinical trials. (C) 2003, Elsevier Science Inc.
Keywords: TIAPROFENIC ACID; INTERSTITIAL CYSTITIS; SURFACE GLYCOSAMINOGLYCANS; ANTIINFLAMMATORY DRUGS; PERMEABILITY BARRIER; CELLS